ACTIVE METHODS OF CHECKING HOMEWORK IN PRIMARY SCHOOL (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Article explores the use of active methods for checking homework in primary school. The work analyzes the theoretical basis of homework as a pedagogical tool and examines innovative ways of its assessment in classroom practice. The study identifies the advantages of active methods – such as peer checking, gamification, and digital platforms – in increasing students’ motivation, responsibility, and self-reflection. Experimental results demonstrate that active methods make the learning process more engaging and effective.